2009
DOI: 10.1111/j.1471-6712.2008.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Can a focused staff training programme improve the ward atmosphere and patient satisfaction in a forensic psychiatric hospital? A pilot study

Abstract: The study indicated that it is possible to improve the ward atmosphere in a desirable direction by a 3-week training programme for nursing staff about important aspects of milieu therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Staff training has also been used to help staff manage distress in the workplace, possibly as a means of improving social climate (Fowler et al 1993). There has also been some related research in other settings -for example a longitudinal three-wave study of nurses showed that those who participated in a staff training program designed to teach them important aspects of milieu therapy were more likely to give positive ratings of the social climate a year after training (Nesset et al 2009). Patients in this study also reported an increase in general satisfaction In some cases, it may not be necessary to change staff perceptions and attitudes before changing behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staff training has also been used to help staff manage distress in the workplace, possibly as a means of improving social climate (Fowler et al 1993). There has also been some related research in other settings -for example a longitudinal three-wave study of nurses showed that those who participated in a staff training program designed to teach them important aspects of milieu therapy were more likely to give positive ratings of the social climate a year after training (Nesset et al 2009). Patients in this study also reported an increase in general satisfaction In some cases, it may not be necessary to change staff perceptions and attitudes before changing behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a myriad of social climate concepts can be found in the management, work and organisational psychology, and medical literatures (e.g., Dollard & Bakker 2009;Garrett & McDaniel 2001;Langdon et al 2004;Langdon et al 2006;Moos & Bromet 1978;Ulrich et al 2007). In some studies no definition of climate is provided (e.g., Howells 2000; Nesset et al 2009;Schalast et al 2008), suggesting that there is a need for researchers to use terminology that is consistent with their approach to measurement, theory, and analysis.…”
Section: Therapeutic Prisonsmentioning
confidence: 99%
“…The need for further staff training is also essential if staff are to improve so that they are "not just giving tablets" (Samarasekera, 2007). This idea of staff training in engaging more therapeutically with patients is very important and has been shown to be successful (Nesset et al, 2009). Staff training is especially important since qualities essential to a good therapeutic relationship include empathy and genuineness, which do not come instinctively to nurses (Moyle, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to consider how they can make the environment more therapeutic in ways other than through this modality. Nesset, Rossberg, Almvik and Friis (2009) concluded from their study that a focused three-week staff-training programme aimed at improving the WA revealed a change in the desired direction for six key subscales o f the WA Scale. In addition, patients reported an increase in satisfaction.…”
Section: Important Aspects Of the Ward Climatementioning
confidence: 99%
“…Ward climate can be seen as a multifactorial construct including the material, social, and emotional conditions of a given ward and the interaction between these factors (Moos, 1989;Tonkin, 2015). Ward climate is found to play a role in therapeutic outcomes like drop out-, release-, and re-admission rates (Moos, Shelton, & Petty, 1973), patient satisfaction (Bressington, Stewart, Beer, & MacInnes, 2011;Middelboe, Schjùdt, Byrsting, & Gjerris, 2001;Nesset, Rossberg, & Almvik, 2009;Rossberg & Friis, 2004), motivation for treatment (van der Helm, Beunk, Stams, & van der Laan, 2014), treatment engagement and therapeutic alliance (Long, Anagnostakis, Fox, Silaule, Somers, West, & Webster, 2011). Climate can be seen as an aspect of program responsivity that enhances treatment effects (Beech & Hamilton-Giachritsis, 2005;Howells & Day, 2003; Ward, Day, Howells, & Birgden, 2004).…”
Section: Introductionmentioning
confidence: 99%